Food-derived bioactive oligopeptide iron complexes ameliorate iron deficiency anemia and offspring development in pregnant rats - Pan, Wenfei; Gao, He; Ying, Xiaoling; Xu, Caiju; Ye, Xiang; Shao, Yelin; Hua, Mengdi; Shao, Jie; Zhang, Xinxue; Fu, Shaowei; Yang, Min (Frontiers in Nutrition, 2022)
This study aimed to investigate anemia treatment and other potential effects of two food-derived bioactive oligopeptide iron complexes on pregnant rats with iron deficiency anemia (IDA) and their offspring. Rats with IDA were established with a low iron diet and then mated. There were one control group and seven randomly assigned groups of pregnant rats with IDA: Control group [Control, 40 ppm ferrous sulfate (FeSO4)]; IDA model group (ID, 4 ppm FeSO4), three high-iron groups (H-FeSO4, 400 ppm FeSO4; MCOP-Fe, 400 ppm marine fish oligopeptide iron complex; WCOP-Fe, 400 ppm whey protein oligopeptide iron complex) and three low-iron groups (L-FeSO4, 40 ppm FeSO4; MOP-Fe, 40 ppm marine fish oligopeptide iron complex; WOP-Fe, 40 ppm whey protein oligopeptide iron complex). Rats in each group were fed the corresponding special diet during pregnancy until the day of delivery. After different doses of iron supplement, serum hemoglobin, iron, and ferritin levels in rats with IDA were significantly increased to normal levels (P<0.05). Serum iron levels were significantly lower in two food-derived bioactive oligopeptide low-iron complex groups than in the low FeSO4 group (P<0.05). Liver malondialdehyde levels were significantly increased in the three high-iron groups compared with the other five groups (P<0.05), and hemosiderin deposition was observed in liver tissue, indicating that the iron dose was overloaded and aggravated the peroxidative damage in pregnant rats. Liver inflammation was reduced in the three low-iron groups. Tumor necrosis factor α secretion was significantly decreased in all groups with supplemented oligopeptide (P<0.05), with the concentration of tumor necrosis factor α declining to normal levels in the two whey protein oligopeptide iron complex groups. In the marine fish oligopeptide iron complex groups, body length, tail length, and weight of offspring were significantly increased (P<0.05) and reached normal levels. Therefore, food-derived bioactive oligopeptide (derived from marine fish skin and milk) iron complexes may be an effective type of iron supplement for pregnancy to improve anemia, as well as reduce the side effects of iron overload, and improve the growth and nutritional status of offspring.